Insomnia - King, Stephen (Hodder & Stoughton, 2011)
You'll lose a lot of sleep . . . Ralph does. At first he starts waking up earlier. And earlier. Then the hallucinations start - the colours, shapes and strange auras. Not to mention the bald doctors who always turn up at the scene of a death. That's when Ralph begins to lose a lot more than sleep. When he begins to understand why his hitherto mild-mannered friend, Ed, is getting out of control - dangerously so. And why his home town is about to become the new Armageddon . . . Insomnia is a relentless waking nightmare in which the master of horror and suspense guarantees you sure won't rest in peace.